2012
DOI: 10.1093/jjco/hys070
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Acute Adrenal Insufficiency Unmasked During Sunitinib Treatment for Metastatic Renal Cell Carcinoma

Abstract: Sunitinib has recently become a standard treatment for metastatic renal cell carcinoma. However, various adverse events have been reported. We present the first case of clinically evident adrenal insufficiency during sunitinib therapy. A 72-year-old man began sunitinib therapy for bilateral lung and adrenal metastases of renal cell carcinoma. His adrenocorticotrophic hormone level was 93.6 pg/ml (7.2 -63.3 pg/ml) before sunitinib treatment, indicating that subclinical adrenal insufficiency already existed. Fat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 13 publications
(8 reference statements)
0
8
0
Order By: Relevance
“…While initial safety studies of sunitinib failed to demonstrate clinical relevance of adrenal toxicity, Yoshino et al [2] have reported a case of possible sunitinib-associated adrenal insufficiency in the setting of mRCC treatment. This patient received sunitinib therapy for mRCC with bilateral adrenal metastases and pre-treatment ACTH and cortisol levels indicating subclinical hypoadrenalism.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…While initial safety studies of sunitinib failed to demonstrate clinical relevance of adrenal toxicity, Yoshino et al [2] have reported a case of possible sunitinib-associated adrenal insufficiency in the setting of mRCC treatment. This patient received sunitinib therapy for mRCC with bilateral adrenal metastases and pre-treatment ACTH and cortisol levels indicating subclinical hypoadrenalism.…”
Section: Discussionmentioning
confidence: 99%
“…The authors postulated that hypermetabolism secondary to thyroid hormone excess was responsible for unmasking adrenal toxicity. Given the response of adrenal metastases to treatment, the clinical relevance of aforementioned adrenal toxicity was theorised [2].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Like almost all anticancer therapies, fatigue is common among recipients of VEGFr-TKI (Cohen & Oudard, 2012). Instances of severe, acute fatigue in recipients of VEGFr-TKI should be investigated further because rare cases of adrenal insufficiency being unmasked by the effects of VEGFr-TKI therapy have been reported (Yoshino et al, 2012). VEGFr-TKIs are also associated with hypothyroidism (Feldt et al, 2012), and patients who experience fatigue should be evaluated for the need for thyroid hormone replacement therapy.…”
Section: Associated Adverse Events Vascular Endothelial Growth Factormentioning
confidence: 99%